Kenya Economic Report, June 2013, No. 8 : Time to Shift Gears--Accelerating Growth and Poverty Reduction in the New Kenya - World Bank (Washington, DC, 2014)
The report has three main messages. First, the economy is expected to achieve higher growth targets in 2013 (5.7 percent) and 2014 (6 percent) over what it achieved in 2012 (4.6 percent), as a result of the smooth election process. However, the government will need to make a concerted effort, if it wishes to approach the 10 percent annual growth rate foreseen in Vision 2030. The report's second message emphasizes on the steps that the government needs to take to create an enabling framework for significant private sector-led growth. The Government needs to continue to invest in infrastructure, to increase domestic energy production, to address the other bottlenecks that affect the cost of doing business, and to continue following sound monetary and fiscal policies. Finally, the report's third message focuses on the poverty situation in Kenya, noting progress made since 2005, when an estimated 47 percent of the population lived below the poverty line, to the present, where poverty estimates range between 34 and 42 percent, the imprecision resulting from the lack of any recent survey data. The report notes the spatial dimension of poverty, and the poor tend to live in the arid and semi-arid regions in the north and north east. It concludes with thoughts about a poverty reduction strategy, which would emphasize on job creation, enhanced productivity of smallholder farms, strengthening and expanding cash transfer programs, targeted public spending programs to provide quality education to the rural poor, and improved poverty monitoring, so that the government can rapidly see which activities have the greatest impacts on improving the lives of the poor.